2019
DOI: 10.3390/biom9090436
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Inhibition of Hyaluronic Acid Oligosaccharides in Triple-Negative Breast Cancer

Abstract: Hyaluronic acid (hyaluronan, HA) is a critical component of the extracellular matrix and plays an important biological function of interacting with different molecules and receptors. In this study, both odd- and even-numbered HA oligosaccharides (HAOs) with specific degrees of polymerization (DP) were prepared by different hydrochloric acid hydrolyses, and their structures were characterized by means of HPLC, ESI-MS, and NMR. The data show that the odd-numbered HAOs (DP3-11) have a glucuronic acid reducing end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Moreover, the binding of HA oligomers to the CD44 and TLR4 receptors was MW-dependent. It was also found that the high binding energies of these short chains are accompanied by less cell viability . These results can explain the observed metabolic activity of MDA-MB-231 cells incubated with the HA products; however, each lyophilized product is a mixture of chains of different MWs, and the exact effect of each fragment cannot be studied under the current experimental conditions.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, the binding of HA oligomers to the CD44 and TLR4 receptors was MW-dependent. It was also found that the high binding energies of these short chains are accompanied by less cell viability . These results can explain the observed metabolic activity of MDA-MB-231 cells incubated with the HA products; however, each lyophilized product is a mixture of chains of different MWs, and the exact effect of each fragment cannot be studied under the current experimental conditions.…”
Section: Resultsmentioning
confidence: 96%
“…oHA is a degradation product of HA that is widely used in drug delivery systems because it is nontoxic, non-immunogenic, and biocompatible. It also exhibits tumor-targeting capability (Chen et al., 2017 ; Han et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, sodium hyaluronate itself may have the potential to suppress cancer progression and metastasis (23)(24)(25)(26). It has highly metabolized in the lymphatic system, and migrates readily via lymphatic capillaries to regional lymph nodes following injection into breast tumor tissue (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%